Anisomeles tamilnadense (Lamiaceae), a new species from Tamil Nadu, India - Bechu, Punnen Abraham; Ramasubbu, Raju; Spurgeon, Edwin Kirubai Dass; Venkatesh, Palanivel; Kalaiselvan, Karuppasamy (Phytotaxa, 2025)
A new species of Lamiaceae, Anisomeles tamilnadense, is described from Dindigul, Tamil Nadu, India. This species is closely related to A. indica and A. malabarica. However, several features differ, including the ovate-lanceolate and narrowly crenate leaf margin, coloured spathulate bracts, coloured calyx, <100 banded unpigmented corolla hairs and larger stigma lobes. This distinctive combination of traits allows to describe a new species within the genus, contributing to the better knowledge of the flora of the Indian subcontinent.